Device for synchronous measurement of optical rotation angle and phase delay and method thereof - LO, YU-LUNG; LIN, JING-FUNG (2009)
This invention provides a device for synchronous measurement of an optical rotation angle and a phase delay and a method thereof. The device comprises an incident light source, a polarizer, a /2 wave plate, a photo-detector, and a Stokes polarimeter. The method comprises: passing an incident light through the polarizer, a subject to be measured, and the /2 wave plate sequentially; receiving the optical signal by the photo-detector; passing the optical signal through the Stokes polarimeter so as to measure the four Stokes parameters S0, S1, S2, and S3; and calculating the optical rotation angle and the phase delay.